After the Rainy Day: How Private Resources Shape Personal Trajectories following Job Loss and Amplify Racial Inequality. Issue 3 (July 2018) - Gould-Werth, Alix
Using data from in-depth interviews with a diverse group of people who lost jobs between 2007 and 2011, my study identifies the important role of private resource banks—reserves of personal resources such as assets and social connections amassed during more favorable times—following job loss. Without these resources, job losers are unable to move past the struggle to survive and onto recovery (through reemployment, comfortable labor market exit, or buffered labor market failure). Because private resources are unequally distributed by race, Black respondents are less able to leverage these resources toward recovery than their White counterparts. These results suggest that job loss may be a turning point in the life course—like incarceration, childbirth, and eviction—in which racial inequality is magnified and reproduced.